UJI AKTIVITAS ANTIFUNGI EKSTRAK DAUNKEMBANG SEPATU (Hibiscus rosa-sinensis linn) TERHADAP PERTUMBUHAN Trichophyton rubrum SECARA IN VITRO - Lu'lu' Luqyana Fatin (2022)
Hibiscus rosa-sinensis Linn is one of the ornamental plants commonly found in Indonesia. Hibiscus leaves are known to have polyphenolic compounds, flavonoids, and tannins that have the potential as an antifungal. This study was True Experimental, aimed to determine the antifungal activity of hibiscus leaf against Trichophyton rubrum. The extraction was done by using the maceration method and aquadest as a solvent. The experiment research was using the Agar well diffusion method and Saboraud Dextrose Agar as media. The hibiscus leaf extract concentration consisted of 10%, 20%, 30%, 40% and 50%. Ketoconazole 2% was used as a positive control and aquadest was used as a negative control. The conclusion showed that hibiscus leaf extract has antifungal activity and produces an inhibition zone with the following mean: the concentration of 10% produces 0.30 mm, the concentration of 20% produces 2.635 mm, the concentration of 30% produces 7.98 mm, the concentration of 40% produces 9.466 mm and the concentration of 50% produces 10.985 mm. Because, in the phytochemical test, hibiscus leaf extract contains polyphenolic compounds, tannins, and flavonoids. The Mann-Whitney test had p < 0.05, which means that hibiscus leaf extract had significant differences between the different extracts, except for the concentration of 40% toward the concentration of 50%. The most effective concentration of hibiscus leaf aquadest extract in inhibiting the growth of T. rubrum was 50%.